E-book: Práticas docentes na educação de jovens e adultos no ensino personalizado: vivências do Centro de Educação de Jovens e Adultons Prof. Luiz Otávio Pereira – CEEJA/Belém - ALBUQUERQUE, Luciana Pereira (Universidade Federal do Pará, 2021)
This research had as objectives to map and systematize, in an e-book format, teaching practices carried out in the context of personalized teaching of Education of Youth and Adults (EJA) from the Centro de Educação de Jovens e Adultos Prof. Luiz Otávio Pereira – CEEJA/Belém. These practices should contribute to student’s learning by means of dialogue, ethics, affectivity and autonomy dimensions. To reach the objectives, the methodological trajectory was composed by: (i) researches on references from theorists who study EJA and personalized teaching; (ii) a documental research; (iii) a data collection using questionnaires applied to teachers and students; (iv) registers of observations taken during the meetings/classes and informal conversations that could complement my perceptions as a researcher; and (v) a specific validation. The data collected were analyzed and the results reveal not only a teaching staff that is committed to the modality and the students but also reveal that the teaching practice in EJA, when using the dimensions mentioned in the teaching-learning process, makes it possible a bigger involvement of the students in their meetings/classes, because they see the relationship between the content studied and their lives. This active participation occurs even when they face hindrances such as the heterogeneity of the groups, the lack of material resources and the necessity of continued education aimed at the EJA modality, among others. Given the results, the proposed e-book aims to reach a diverse audience in order to socialize the successful activities that can be shared by other teachers.